A Strategy to Simultaneously Cure Type 1 Diabetes and Diabetic Nephropathy by Transplant of Composite Islet-Kidney Grafts - Pomposelli, Thomas; Schuetz, Christian; Wang, Ping; Yamada, Kazuhiko (Frontiers in Endocrinology, 2021)
In recent years islet cell transplant has proven itself to be a viable clinical option for a select group of diabetic patients. Graft loss after transplant however continues to hinder the long-term success of the procedure. Transplanting the islets as a pre-vascularized composite islet-kidney graft has emerged as a relevant solution. Much groundbreaking research has been done utilizing this model in conjunction with strategies aimed towards islet cell survival and prolongation of function in the host. Transplanting the islet cells as a prevascularized graft under the capsule of the donor kidney as a composite islet-kidney graft has been shown to provide long term durable blood glucose control in large animal studies by limiting graft apoptosis as well as providing a physical barrier against the host immune response. While promising, this technique is limited by long term immunosuppression requirements of the host with its well-known adverse sequelae. Research into tolerance inducing strategies of the host to the allogeneic and xenogeneic islet-kidney graft has shown much promise in the avoidance of long-term immunosuppression. In addition, utilizing xenogeneic tissue grafts could provide a near-limitless supply of organs. The islet-kidney model could provide a durable and long-term cure for diabetes. Here we summarize the most recent data, as well as groundbreaking strategies to avoid long term immunosuppression and promote graft acceptance.